The binding of the rat liver thyroid hormone nuclear receptor to deoxyribonucleic acid using a gel filtration assay - Ricketts, M. H.(Michael Hugh) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1979.